Treatment Outcome of Remdesivir Compared to Favipiravir on Moderate Symptoms COVID-19 - Arifin, Arief Riadi; Yunus, Faisal; Patrama, Satria; Putra, Muhammad Ryan Adi; Roxanne, Olivia Geraldine (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2023)
Remdesivir and Favipiravir have been widely used as antiviral agents in treating COVID-19. However, studies providing head on comparison of treatment outcomes between the two antiviruses are rare. The aim of this study is to compare the treatment outcome of Remdesivir and Favipiravir in moderate symptoms COVID-19. Subjects were divided into two groups based on received antivirus during COVID-19 treatment in the hospital, Remdesivir group and Favipiravir group. Post-treatment outcome was measured with three indicators: symptom improvement, negative conversion of RT-PCR, and radiological improvement. Outcomes of both groups were compared with chi square test with Remdesivir serves as a risk factor and Favipiravir as control. Out of a total of 130 subjects, 65 received Remdesivir, and 65 received Favipiravir. Post-treatment RT-PCR and radiologic examination were performed on a median of Day-10 hospitalization. RT-PCR conversion to negative was significantly more likely in Remdesivir group (RR: 1,917, 95% Cl 1,044 – 3,518, p = 0.047, chi square test). There was no significant difference between Remdesivir group and Favipiravir group in symptom improvement on Day-5 (RR 0.941, 95% Cl 0.776 – 1,141), nor Day-7 (RR 1.020, 95% Cl 0.855 – 1.216). There was also no significant difference in radiological improvement (RR 0.855, 95% Cl 0.712 – 1.026). Administering remdesivir to COVID-19 patients significantly increased the occurrence of negative RT-PCR conversion after therapy compared to standard favipiravir therapy.